Comparative effectiveness of endoscopic and microscopic adenoma removal in acromegaly - Vassilyeva, Natalya; Mena, Natmir; Kirov, Kiril; Diatlova, Ekaterina (Frontiers in Endocrinology, 2023)
Somatotropinomas are the main cause of acromegaly. Surgery is the primary and most efficient method of treatment. The study aimed to compare the radicality of small-sized and medium (<30 mm) somatotropinoma removal and the incidence of postoperative complications in patients with acromegaly when using microscopic and endoscopic techniques. In this randomized controlled trial, a total of 83 patients with acromegaly underwent transspheroidal endoscopy or microscopic surgery. Somatotropinoma was the cause of acromegaly in all cases. Patients were randomly divided into two comparison groups depending on the applied surgical technique. Group 1 (n = 40) consisted of patients who underwent adenomectomy with transnasal transsphenoidal access by a microscope. Group 2 (n = 43) included patients who underwent the same surgical procedure with an endoscope. The following indicators were assessed: radicality of tumour removal, treatment effectiveness, postoperative complications, and remission rate. The study has shown that removal of somatotropinoma in patients with acromegaly using endoscopic technique increases the radicality of tumour removal in comparison with microscopic technique. Total removal of somatotropinoma was successful in 88.4% of cases when using the endoscopic technique. Secondly, the segmentation of patients according to their tumour characteristics poses challenges, primarily owing to the rarity of acromegaly as a disease. The difference between groups was not statistically significant (p=1.02). There were no statistically significant differences in basal GH level and IGF-1 level between groups (p=0.546 and p=0.784, respectively). Endonasal transsphenoidal endoscopic adenomectomy is proven efficacy, a less traumatic degree, and higher somatotropinoma removal radicality. Both surgical methods lead to disease remission.